Desenvolvimento de um sensor híbrido-inclinação + EMG, para aplicações em robótica e fisioterapia - Bôrtole, Magdo (2011)
Equipments used to capture EMG signals are usually expensive and difficult to use in environments outside laboratories. This paper describes the development of a hybrid sensor capable of capturing myoelectric and inclination signals, provided by a pair of differential electrodes and a three-axis accelerometer as sensor devices. The information captured by the hybrid sensor can be used for biomechanical analysis of human movement, and is transmitted via Bluetooth communication, leaving the sensor free of wires and cables. The hybrid sensor has applications both in Robotics as Physiotherapy. In Robotics it has been used as a standalone system for controlling a robotic wheelchair for disabled people, through the user's head movements, achieving good results. Also in Robotics, it was used to control a small robot with a gripper, in a project to assist children with severe physical disabilities. In the area of Physical Therapy it has many applications where the collection of EMG signals is required, and was used to detect tilting of body parts in Physiotherapy. In its final state, the hybrid sensor consists of a portable electronic device, wireless, small, lightweight, highly autonomous, with high calculation capacity and high rate of data transmission. These features allow its use outside laboratories, expanding the application area.